Manuel pratique pour initier les enfants à la connaissance de l’importance des NUS au Burkina Faso. Manuel de l’enseignant - Tognoli, Flora; Borelli, Teresa; Grazioli, Francesca (2024)
This manual serves as a teacher's guide to help primary school students appreciate Neglected and Underutilized Species (NUS) – food species that are culturally significant and locally adapted, with notable nutritional value. Created within the framework of the EU-funded SUSTLIVES project, this educational resource is the first to establish a methodology for introducing NUS in the classroom to strengthen messaging on the protection of agrobiodiversity. It employs a participatory and inclusive approach, taking into account both gender and age, and offers practical guidance for teachers aiming to engage children and raise their awareness of the importance of NUS. Although originally designed for Burkina Faso and Niger, it can be adapted for use in other regions.